Application of Computer Network-aided Teaching Mode in English Translation Teaching at Colleges and Universities. Issue 2 (October 2020) - Min, Jun
Abstract: The improvement of teaching quality and level of translation courses for non-English major students at colleges and universities has been subject to the constraints of factors such as short teaching time, a large number of students taking the course, uneven levels of student, unitary teaching method, etc. The existing problems in the English translation teaching mode at colleges and universities are analyzed to explore how to implement computer network-aided teaching in English translation courses at colleges and universities, thereby improving the effect of translation teaching and comprehensive competence of students to use English. The computer network-aided teaching mode mainly emphasizes three links (situational language teaching, interactive approach of learning and application, participation in teaching). Teachers can inspire and guide students to transform knowledge into their abilities through the design of teaching situations so that students can truly "learn" by "doing".